What Children Learn From Television Programmes: The Case of Serdang Area, Selangor - Omer, Mutaz Osman (1999)
The primary objective of this study was to find out what children learn from TV programmes. The specific objectives were: (a)to explore children's favourite TV programmes (b)to determine the extent of children's TV viewing (c)to ascertain whether parents control over their children's TV viewing (d)to find out the benefits of TV viewing for children as perceived and (e)find out the type of skills that children acquire as a result of watching TV programmes. The study was conducted on 200 children at three grade levels--70 third graders, 64 seventh graders and 66 eleventh graders--in the public schools of Serdang. Data were collected through questionnaires and analysed using SPSS program to compute the frequency distributions percentage and cross tabulation. The results indicated that children acqUIre skills as result of watching TV programme, such as academic, motor and social skills. They learn some factual knowledge from programmes; much of this knowledge learned from programmes, which are not educational by design. They learn facts which are interesting to them but which may or may not have utility for personal success in school. They also learn to perform sequences of behaviour and they may actualise these behaviours in subsequent interaction with peers. However, the study showed that the parents are the major factor in controlling what programmes their children watch. The results indicated that the parents paid attention on which programmes and what the type of programmes their children can watch. The study focuses on the topics of restoration for the children to adapt method of learning. Therefore, parents, teachers and government should devote their attention in selecting and showing the programmes.